Lipid Peroxidation and Iron Metabolism: Two Corner Stones in the Homeostasis Control of Ferroptosis - Rochette, Luc; Dogon, Geoffrey; Rigal, Eve; Zeller, Marianne; Cottin, Yves; Vergely, Catherine (International journal of molecular sciences, 2022)
Regulated cell death (RCD) has a significant impact on development, tissue homeostasis, and the occurrence of various diseases. Among different forms of RCD, ferroptosis is considered as a type of reactive oxygen species (ROS)-dependent regulated necrosis. ROS can react with polyunsaturated fatty acids (PUFAs) of the lipid (L) membrane via the formation of a lipid radical L• and induce lipid peroxidation to form L-ROS. Ferroptosis is triggered by an imbalance between lipid hydroperoxide (LOOH) detoxification and iron-dependent L-ROS accumulation. Intracellular iron accumulation and lipid peroxidation are two central biochemical events leading to ferroptosis. Organelles, including mitochondria and lysosomes are involved in the regulation of iron metabolism and redox imbalance in ferroptosis. In this review, we will provide an overview of lipid peroxidation, as well as key components involved in the ferroptotic cascade. The main mechanism that reduces ROS is the redox ability of glutathione (GSH). GSH, a tripeptide that includes glutamic acid, cysteine, and glycine, acts as an antioxidant and is the substrate of glutathione peroxidase 4 (GPX4), which is then converted into oxidized glutathione (GSSG). Increasing the expression of GSH can inhibit ferroptosis. We highlight the role of the xc- GSH-GPX4 pathway as the main pathway to regulate ferroptosis. The system xc-, composed of subunit solute carrier family members (SLC7A11 and SLC3A2), mediates the exchange of cystine and glutamate across the plasma membrane to synthesize GSH. Accumulating evidence indicates that ferroptosis requires the autophagy machinery for its execution. Ferritinophagy is used to describe the removal of the major iron storage protein ferritin by the autophagy machinery. Nuclear receptor coactivator 4 (NCOA4) is a cytosolic autophagy receptor used to bind ferritin for subsequent degradation by ferritinophagy. During ferritinophagy, stored iron released becomes available for biosynthetic pathways. The dysfunctional ferroptotic response is implicated in a variety of pathological conditions. Ferroptosis inducers or inhibitors targeting redox- or iron metabolism-related proteins and signal transduction have been developed. The simultaneous detection of intracellular and extracellular markers may help diagnose and treat diseases related to ferroptotic damage.